Development And Characterization Of Nanofibers From Kenaf Bast To Reinforce Polymer Composites - Davoudpour, Yalda (2014)
The aim of this research was to explore the combination of hydrochloric acid (hc1) nonhydrolysis and high pressure homogenization as a new process to isolate cellulose nanofiber (cnf). In order to prepare cnf firstly soda-anthraquinon pulping and alkaline hydrogen peroxide bleaching was performed to remove lignin and hemicellulose as well as to separate single fibers. Subsequently, the acid hydrolysis was applied as a pretreatment at different time to reduce the size of fibers and to prevent from clogging of the homogenization. The best hydrolysis condition was selected to prepare the cnf. Then cnf was isolated using high pressure homogenization at various cycle and suspension concentrations. The structural analysis of the fibers before and after each treatment was conducted by x-ray diffraction (xrd) and fourier transform infrared spectroscopy (ft-ir). Also, the morphological properties of the fibers was studied by scanning electron microscopy (sem), atomic force microscopy (afm) and transmission electron microscopy (tem) and the thermal characteristics was analyzed by thennogravimetric analysis (tga) and differential scanning calorimetry (dsc).